Value Processing Information System in SMAN 09 Bengkulu City - Surya Ade Saputera; Vike Juzeplin; Monsya Juansen (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
Value is one important component in teaching and learning activities in schools that will be input into output is expected to be offset even develop each student’s grades. One is starting measuring student learning outcomes assessment that is usually handled by each homeroom brackish. Conducted a thorough assessment and continuous on the process and learning outcomes in accordance with the characteristics of subjects and majors they choose to obtain complete information value, from the way the values processing still done using a program that has not been integrated with the database. Problems that occur in the processing of report cards in SMAN 09 KOTA BENGKULU is still writeen in the book report cards, and delivering value is still using paper media, so a lot of time and effort required to process the value. This reserch has resulted in a processing systems that helps the value of the work of the teachers and homeroom, Web-Based Information Systems that use assistive technologies such as PHP and the MySQL database to provide convenience for the admin in this case the class teacher / teachers and students to access the device through for any network connected to the internet. This is done to bulid a system that helps in the processing and presentation of student data information. With the aim of processing the value that can be processed effectively and efficiently, so that it can directly access and information can be conveyed properly.